Examination of adolescents' negative thoughts, depressive mood, and family environment - (:unkn) unknown (LIBRA PUBLISHERS INC, 2001)
The focus of this study was the relationship among adolescents' negative thoughts, depressive mood, and family environment. Three hundred eleven students (aged 16 and 17 years) in public and private schools served as subjects. They were administered the Family Environment Scale, the Automatic Thoughts Questionnaire, and the Deck Depression Inventory. Family cohesion was found to be related to the degree of negative thoughts and depressive mood of the adolescents, but perceived control within the family was not.